2017
DOI: 10.1126/scitranslmed.aah3438
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with CTLA4-Ig and an antiviral monoclonal antibody controls chikungunya virus arthritis

Abstract: In 2013, chikungunya virus (CHIKV) transmission was documented in the Western Hemisphere, and the virus has since spread throughout the Americas with more than 1.8 million people infected in more than 40 countries. CHIKV targets the joints, resulting in symmetric polyarthritis that clinically mimics rheumatoid arthritis and can endure for months to years. At present, no approved treatment is effective in preventing or controlling CHIKV infection or disease. We treated mice with eight different disease-modifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 40 publications
3
61
0
Order By: Relevance
“…Abatacept, a human IgG fusion protein paired with a CTLA‐4 extracellular domain motif, prevents antigen‐presenting cells from delivering costimulatory signals to T cells. In the study by Miner et al, abatacept reduced T cell accumulation in the joints of infected mice and, in combination with an anti–chikungunya virus neutralizing antibody, abolished signs of inflammatory disease and markedly reduced levels of chemokines, proinflammatory cytokines, and infiltrating leukocytes . Notwithstanding the promising preclinical outcomes and innovative approaches, these candidate therapies, along with the other examples cited earlier in this review (summarized in Figure ), warrant further evaluation in the treatment of chikungunya virus–induced joint pathologies in a clinical setting, keeping in mind the potential risk of immunosuppression when targeting host response mechanisms.…”
Section: Clinical Care Of Chikungunya Virus Patients: Lessons Learnedmentioning
confidence: 79%
See 1 more Smart Citation
“…Abatacept, a human IgG fusion protein paired with a CTLA‐4 extracellular domain motif, prevents antigen‐presenting cells from delivering costimulatory signals to T cells. In the study by Miner et al, abatacept reduced T cell accumulation in the joints of infected mice and, in combination with an anti–chikungunya virus neutralizing antibody, abolished signs of inflammatory disease and markedly reduced levels of chemokines, proinflammatory cytokines, and infiltrating leukocytes . Notwithstanding the promising preclinical outcomes and innovative approaches, these candidate therapies, along with the other examples cited earlier in this review (summarized in Figure ), warrant further evaluation in the treatment of chikungunya virus–induced joint pathologies in a clinical setting, keeping in mind the potential risk of immunosuppression when targeting host response mechanisms.…”
Section: Clinical Care Of Chikungunya Virus Patients: Lessons Learnedmentioning
confidence: 79%
“…Combined therapy with biologic agents. A recent study by Miner et al sought to target both humoral and adaptive arms of the immune response by using abatacept, a drug approved in 2005 by the FDA for the treatment of RA, in combination with an anti–chikungunya virus neutralizing antibody, and assessed their ability to decrease acute joint swelling in chikungunya virus–infected mice . Abatacept, a human IgG fusion protein paired with a CTLA‐4 extracellular domain motif, prevents antigen‐presenting cells from delivering costimulatory signals to T cells.…”
Section: Clinical Care Of Chikungunya Virus Patients: Lessons Learnedmentioning
confidence: 99%
“…These study findings may have important clinical relevance for chikungunya virus in the Americas. Since there is no current standard of care guidance for treatment of chikungunya arthritis, some patients are currently being treated with immunosuppressive agents such as methotrexate , hydroxychloroquine , etanercept , adalimumab , sulfasalazine , fingolimod , abatacept, and tofacitinib . This practice could be potentially harmful in the setting of replicating virus in the synovium since it could permit re‐emergence of a systemic viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…"Targeting T cells is emerging as a promising strategy for the treatment of chikungunya arthritis. Two independent experimental studies demonstrated the efficacy of abatacept and fingolimod in amelioration of disease when targeting pathogenic CD4+ T. 66,67 Therapeutic management of other musculoskeletal disorders (non CIR): Treatment should always be optimized by combining an analgesic, a NSAID, a local anti-inflammatory therapy in resistant sites (including joint or peritendinous infiltration), and physical therapy. The therapeutic effectiveness can be assessed in the medium term, for several weeks.…”
Section: Therapeutic Managementmentioning
confidence: 99%